2019
DOI: 10.1111/os.12436
|View full text |Cite
|
Sign up to set email alerts
|

Bone Hardness of Different Anatomical Regions of Human Radius and its Impact on the Pullout Strength of Screws

Abstract: Objective To investigate the bone hardness of different anatomical regions of the human radius and its impact on the pullout strength of screws. Methods Fresh radius bones were obtained from three donated cadavers. They were divided into three parts: proximal metaphysis, shaft, and distal metaphysis. The proximal metaphysis contains the head, neck, and radial tuberosity. The distal metaphysis includes the palmaris radius and the styloid process. The shaft of the radius was divided into nine segments of equal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…In the femur, the cortical bone was hardest in the middle of the diaphysis with hardness values around 15‐21% higher than the proximal and distal regions, but this was not replicated in the humerus where cortical bone in the distal region was significantly harder than the proximal region (Figure 4). This mirrors the patterns observed in earlier work on human cortical bone where Evans & Lebow (23) found that the human femur is also hardest in the middle third of the shaft, and the work by Wu et al who found similar patterns of hardness in the human radius (22). Weaver (15) noted little variation in hardness along the length of the diaphyseal region of the human fibula but found a “pronounced” decrease in hardness in the metaphyseal and epiphyseal region.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the femur, the cortical bone was hardest in the middle of the diaphysis with hardness values around 15‐21% higher than the proximal and distal regions, but this was not replicated in the humerus where cortical bone in the distal region was significantly harder than the proximal region (Figure 4). This mirrors the patterns observed in earlier work on human cortical bone where Evans & Lebow (23) found that the human femur is also hardest in the middle third of the shaft, and the work by Wu et al who found similar patterns of hardness in the human radius (22). Weaver (15) noted little variation in hardness along the length of the diaphyseal region of the human fibula but found a “pronounced” decrease in hardness in the metaphyseal and epiphyseal region.…”
Section: Discussionsupporting
confidence: 87%
“…The hardness of the porcine adult femur (52.23 ± 1.00 kg mm −2 ) was similar to the values for cortical bone from the femora of sows reported in the literature of 53.5‐61.6 kg mm −2 (17). The hardness of cortical bone from the adult porcine femur and humerus was comparable to the hardness of adult (aged 35) human fibular cortical bone (55.1 kg mm −2 ) as determined by Weaver (15), human iliac and calcaneal bone (49.30 kg mm −2 ) from older adults free from apparent bone disease (21), and by Wu et al for human radial diaphyses (43.82 mm −2 ) (22). Comparable hardness for human (39.4 kg mm −2 ) and porcine (37.1 kg mm −2 ) cortical bone has also been reported by Saville et al (13), although the values were somewhat lower than those reported in the literature for porcine and human bone, and those observed in this study.…”
Section: Discussionsupporting
confidence: 66%
“…Collagen cross-link formation is thought to affect the mechanical properties of bone at a material level [ 19 , 20 ]. The heterogeneity of bone porosity, collagen fiber orientation, density and mineralization lead to a gradient of bone material properties and can have a strong effect on the structural performance of bone [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hardest part of the radius was the shaft, with a value of 42 ± 6 HV. The proximal metaphysis had a hardness value of 34 ± 6 HV, and the distal metaphysis hardness value was 35 ± 5 HV [ 61 , 62 , 63 ]. Generally, the hardness of material is related to its atomic mobility capacity, distortion of crystalline lattice and atomic displacement.…”
Section: Resultsmentioning
confidence: 99%